Anti-frequency-offset algorithm on single-channel blind separation of burst GMSK mixed signals - Can-hui LIAO; Shi-long TU; Jian WAN (Tongxin xuebao)
A per-survivor processing (PSP) based anti-frequency-offset algorithm was proposed for single-channel blind separation of burst GMSK mixed signals.The algorithm traces the phase changes caused by frequency offset and channel changes caused by other matters separately,which remarkably tones up the capacity against frequency offset.Simulation results show that the proposed algorithm can work well even when the unitary frequency offset (compared to symbol rate ) grows up to 1.5×10−2,while the traditional PSP algorithm needs the unitary frequency offset less than 2.0×10−4.Further-more,the proposed algorithm has no need for phase initialization,and a loss of only 1dB on performance can be achieved in comparison with the traditional PSP algorithm.